Altered trophic interactions in warming climates: consequences for predator diet breadth and fitness. Issue 1914 (30th October 2019) - Bestion, Elvire; Soriano-Redondo, Andrea; Cucherousset, Julien; Jacob, Staffan; White, Joël; Zinger, Lucie; Fourtune, Lisa; Di Gesu, Lucie; Teyssier, Aimeric; Cote, Julien
Abstract : Species interactions are central in predicting the impairment of biodiversity with climate change. Trophic interactions may be altered through climate-dependent changes in either predator food preferences or prey communities. Yet, climate change impacts on predator diet remain surprisingly poorly understood. We experimentally studied the consequences of 2°C warmer climatic conditions on the trophic niche of a generalist lizard predator. We used a system of semi-natural mesocosms housing a variety of invertebrate species and in which climatic conditions were manipulated. Lizards in warmer climatic conditions ate at a greater predatory to phytophagous invertebrate ratio and had smaller individual dietary breadths. These shifts mainly arose from direct impacts of climate on lizard diets rather than from changes in prey communities. Dietary changes were associated with negative changes in fitness-related traits (body condition, gut microbiota) and survival. We demonstrate that climate change alters trophic interactions through top-predator dietary shifts, which might disrupt eco-evolutionary dynamics.